2020
DOI: 10.1007/s11676-020-01156-0
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific biomass allometric models and expansion factors for indigenous and planted forests of the Mozambique highlands

Abstract: Secondary Miombo woodlands and forest plantations occupy increasing areas in Mozambique, the former due to anthropogenic activities. Plantations, mainly species of Eucalyptus and Pinus, are being established on sites previously covered by secondary Miombo woodlands. This affects the evolution, cycle and spatiotemporal patterns of carbon (C) storage and stocks in forest ecosystems. The estimation of C storage, which is indispensable for formulating climate change policies on sequestrating CO2, requires tools su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 87 publications
1
8
1
Order By: Relevance
“…The highest percentage of carbon content was observed in stem (44.1%), followed by branch (42.3%) and foliage (34.1%) (Table 2). This finding was different from previous studies that assumed the percentage of carbon content in eucalyptus biomass around 50% (Latifah et al, 2018;Viera and Rodríguez-Soalleiro, 2019;Wirabuana et al, 2019;Magalhães et al, 2020). In general, the variation of carbon storage in tree species was influenced by certain factors, including age, site quality, and genetics.…”
Section: Figure 2 Distribution Of Sample Trees In Every Diameter Classcontrasting
confidence: 90%
“…The highest percentage of carbon content was observed in stem (44.1%), followed by branch (42.3%) and foliage (34.1%) (Table 2). This finding was different from previous studies that assumed the percentage of carbon content in eucalyptus biomass around 50% (Latifah et al, 2018;Viera and Rodríguez-Soalleiro, 2019;Wirabuana et al, 2019;Magalhães et al, 2020). In general, the variation of carbon storage in tree species was influenced by certain factors, including age, site quality, and genetics.…”
Section: Figure 2 Distribution Of Sample Trees In Every Diameter Classcontrasting
confidence: 90%
“…Magalhães et al (2020) reported that the stem density of miombo woodlands and tree plantations in the study area was ≤200 and >1000 ha –1 , respectively, and Guedes, Olsson, Sitoe, & Egnell (2018) reported that litterfall in tree plantations was double that of miombo woodlands. Stand density contributes to maximizing litter production (Bahru & Ding, 2020; Kara et al, 2008; Will et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…This also explains why younger (<25 years) and second‐rotation plantations had larger values of BD compared with the older (>50 years) and the first‐rotation plantations, since the former have less canopy cover than the latter, leading to a relatively limited capacity of intercepting rainfall. The study area is vulnerable to splash erosion due to steep slopes and intense rainfall; however, miombo woodlands and younger plantations are more vulnerable due to open forest canopy, scarce litter layer (Guedes, Olsson, Sitoe, & Egnell, 2018), and understory vegetation (Magalhães et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We also used model precision (V, Eq. ( 6)) statistics 51 . We considered the model with the lowest MAPE, V, AIC, and highest AICw the best-fitting model.…”
Section: Model Evaluation and Validationmentioning
confidence: 99%